Principal and Teacher Collaboration: An Exploration of Distributed Leadership in Professional Learning Communities - DeMatthews, David E. (International Journal of Educational Leadership and Management, 2014)
Professional learning communities (PLCs) can be powerful tools for school improvement but require principals and teachers to collaborate and work together.  This article reports on a qualitative multi-case study focused on six elementary schools in West Texas that had been identified for having effective PLCs.  Principals and teachers were observed and interviewed over the course of one academic school year to understand how leadership was distributed across the school to facilitate effective PLCs.  Findings highlight the ways principals distribute leadership across their school, relevant teacher and principal interactions, and how key aspects of PLCs are influenced by principals, teacher leaders, and teachers.   Findings have implications for in-service professional development experts within school districts and faculty working in principal preparation programs.